UPAYA MENINGKATKAN JUMLAH PENGUNJUNG DI SITUS TAMAN PURBAKALA DALAM MENDUKUNG KESEJAHTERAAN MASYARAKAT PUGUNG RAHARJO, LAMPUNG TIMUR LAMPUNG - Shodikin; Damanhuri (EKSYDA: Jurnal Studi Ekonomi Syariah, 2023)
Abstract The research carried out by the author was entitled "Efforts to Increase the Number of Visitors at the Archaeological Park Site to Support the Welfare of the Pugung Raharjo Community, East Lampung, Lampung." The research carried out has the aim of exploring efforts to increase the number of visitors at ancient park sites by analyzing and identifying using display, geographic, facility and security methods.